The principle of the power of will and its effect in the commercial lease contract - Badache, Saad (Journal of Human Sciences, 2022)
The contract’s principal is  when  the parties are being  free  to  establish and arrange the effects, by taking  in to account  the  following   public  order  and  morals,  in addition to  some  mandatory  provisions  prescribed  by the legislator which  regulate  the  contract,  and  whether  most  special   rules of a  particular  contract are initiatively  considered  as interpretative  rules, to be  applied  if  they  have not  been agreed,  by to the  contractor  thus  contrator’s  desire is to set up  legal  conduct,  and  determine  its  effects this  infact is the principle of  the  authority’s, whill  in  which  the  contract is based  on the  principal  of “ pacta sunt servanda “ legal conduct  is determined,  by  both the  will  and  agreement of the  contracting  parties,  one  of  the  most  important  contracts that  the  will  has  played a  crucial  role in  regulating  them,  is  the  contract  of  the  commercial  lease that we are considering , However this  has not prevented the legislator  from  interfering the legislator,  may interfere by establishing  legal controls,  in order  to  provide  legal protection  to  both  the  lessor  and the less.